2020
DOI: 10.1038/s41598-020-68811-8
|View full text |Cite
|
Sign up to set email alerts
|

Dual SMAD inhibition and Wnt inhibition enable efficient and reproducible differentiations of induced pluripotent stem cells into retinal ganglion cells

Abstract: Glaucoma is a group of progressive optic neuropathies that share common biological and clinical characteristics including irreversible changes to the optic nerve and visual field loss caused by the death of retinal ganglion cells (RGCs). The loss of RGCs manifests as characteristic cupping or optic nerve degeneration, resulting in visual field loss in patients with Glaucoma. Published studies on in vitro RGC differentiation from stem cells utilized classical RGC signaling pathways mimicking retinal development… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 63 publications
2
34
0
Order By: Relevance
“…In order to promote RGC survival and functional maturation, retinal organoids have been dissociated at D56, a stage of development at which many RGCs are present, and retinal cells were replated onto an adherent substrate. In agreement with previous studies, the adherent culture of retinal cells allowed RGCs to grow extensions showing βIII-tubulin or THY1 immunoreactivity (Ohlemacher et al, 2016;Li et al, 2017;Fligor et al, 2018;Langer et al, 2018;Chavali et al, 2020). The capacity of neurons such as RGCs to trigger an action potential depends on different hallmarks including the expression of specific voltage-gated channels and, importantly, a resting membrane potential (V rest ) allowing their activation (Catterall, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In order to promote RGC survival and functional maturation, retinal organoids have been dissociated at D56, a stage of development at which many RGCs are present, and retinal cells were replated onto an adherent substrate. In agreement with previous studies, the adherent culture of retinal cells allowed RGCs to grow extensions showing βIII-tubulin or THY1 immunoreactivity (Ohlemacher et al, 2016;Li et al, 2017;Fligor et al, 2018;Langer et al, 2018;Chavali et al, 2020). The capacity of neurons such as RGCs to trigger an action potential depends on different hallmarks including the expression of specific voltage-gated channels and, importantly, a resting membrane potential (V rest ) allowing their activation (Catterall, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…This crucial point is illustrated by a recent study showing that only hiPSC-derived RGCs displaying an adequately negative V rest were able to spike (Teotia et al, 2019). In the present study, the V rest was approximatively −43 mV, a slightly more depolarized value than that reported by Riazifar et al (2014) or Chavali et al (2020) in hiPSC-derived RGC-like cells, but lower than that observed by Teotia et al (2019). Consistent with previous studies (Teotia et al, 2019;VanderWall et al, 2019), we demonstrated that 3 weeks after plating, the mature RGCs, in contrast to photoreceptors, displayed voltage-gated ionic currents enabling these RGCs to evoke spikes after stimulation and to spontaneously fire.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…They generated over 80% of the pure RGC cultures in about 40 days and purified the Thy1+ cells thanks to the unique expression of the surface glycoprotein Thy1 in the RGCs. Employing magnetic-activated cell sorting (MACS) and CD90.2 microbeads, they obtained 95% of the cells positive for BRN3A [ 89 ]. In all these differentiation protocols, elongated axons were observed.…”
Section: Applications Of Ipsc-derived Rgcsmentioning
confidence: 99%
“…Cells were washed in 1X PBS and mounted with prolong gold mounting medium with DAPI for nuclei staining. Images were captured by Olympus FV1000 Confocal microscope with the use of appropriate filters and lasers [35].…”
Section: Immunostainingmentioning
confidence: 99%